2005
DOI: 10.1002/cyto.a.20169
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of detection specificity of Plasmodium‐infected murine erythrocytes by flow cytometry using autofluorescence and YOYO‐1

Abstract: Background: Microscopic analysis of blood smears is currently the most frequently used method to measure parasitemias in experiments of drug efficacy in murine models of malaria. However, it is subjective and labour intensive, which preclude its utilization in large-scale evaluation programs. Flow cytometry is an alternative method, but due to the limited specificity achieved with the currently available techniques, it has not been widely used in murine models of malaria during preclinical evaluation. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 32 publications
5
79
2
Order By: Relevance
“…After having analyzed 242 samples from infected rats in the experiments during our methodological evaluation, we found that most of the parasitemias read by FCM were, on average, 14% higher than the counts of microscopy. The differences observed may be explained by the fact that microscopy is a subjective technique and many cells that do not show a healthy morphology may be discarded during counting, whereas FCM detects parasites irrespective of their health status (12). In fact, we found some schizontlike cells attached to the membrane of normal RBCs (Fig.…”
Section: Accuracy Of Fcm Compared To Microscopymentioning
confidence: 87%
See 4 more Smart Citations
“…After having analyzed 242 samples from infected rats in the experiments during our methodological evaluation, we found that most of the parasitemias read by FCM were, on average, 14% higher than the counts of microscopy. The differences observed may be explained by the fact that microscopy is a subjective technique and many cells that do not show a healthy morphology may be discarded during counting, whereas FCM detects parasites irrespective of their health status (12). In fact, we found some schizontlike cells attached to the membrane of normal RBCs (Fig.…”
Section: Accuracy Of Fcm Compared To Microscopymentioning
confidence: 87%
“…Therefore, the nucleated blood cells can easily be distinguished from infected cells on the basis of the difference in the fluorescence intensity (25). These features make YOYO-1 an extremely sensitive nucleic acid dye compared with many of the aforementioned dyes, a property that can be very useful in FCM (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations